Sir John Fielding (1721–80) we współczesnym kryminale anglojęzycznym - Lipski, Jakub (Zagadnienia Rodzajów Literackich, 2020)
This article discusses the ways in which the life and achievements of Sir John Fielding are reconstructed in contemporary crime fiction in English. The material under scrutiny consists of selected examples of the so-called Georgian crime/mystery, that is, crime narratives set in Georgian England (1714–1837, the reign of George I, George II, George III and George IV). The discussed works include those in which Fielding functions as a secondary character — the series Dr. Sam: Johnson, Detector by Lillian de la Torre and The Demoniacs by John Dickson Carr — as well as those in which he becomes the protagonist — the series Sir John Fielding Mysteries (Bruce Alexander, 1994–2005) and John Rawlings Mysteries (Deryn Lake, 1994–2000). The offered reading of these texts is contextualized historically as well as being informed by Michel Foucault’s ideas put forward in Discipline and punish.